Insights into intestinal barrier disruption during long-term gut Chlamydia colonization in mice: a single-cell transcriptomic approach - Wan, Ziqing; Jiang, Yicun; Xie, Sheng; Wan, Jiao; Huang, Youyou; Wang, Luying; Zhang, Qi; Zhou, Zengzi; Sun, Xin; Shu, Chuqiang; Zhang, Tianyuan; Tian, Qi (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionChlamydia trachomatis, a leading cause of sexually transmitted bacterial infections in women, is increasingly recognized for its potential to colonize the gastrointestinal tract as a long-term reservoir. However, the mechanisms enabling its persistence in the gut remain poorly understood, hindering the development of effective treatments for chronic infections.MethodsWe employed single-cell RNA sequencing (scRNA-seq) to analyze gene expression profiles and cellular heterogeneity in mouse colonic tissues during Chlamydia long-term colonization to characterize transcriptional changes and intercellular interactions critical for bacterial persistence.ResultsOur analysis revealed significant alterations in gene expression across intestinal cell populations, with distinct molecular pathways implicated in Chlamydia persistence. Key findings included downregulation of epithelial tight junction markers, suggesting compromised intestinal barrier integrity, which may facilitate bacterial invasion. Additionally, we observed dysregulation of goblet cell transcriptional networks and disrupted immune-epithelial cell communication, indicating potential mechanisms for bacterial survival.DiscussionThese findings highlight how Chlamydia may exploit host cell pathways to establish long-term colonization in the gut. The impairment of epithelial barrier function and altered cellular crosstalk provide novel insights into its persistence strategies. Understanding these mechanisms could inform future therapeutic approaches targeting chronic Chlamydia infections.